2014
DOI: 10.11622/smedj.2014051
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia repair: are the results from a general hospital comparable to those from dedicated hernia centres?

et al.

Abstract: A general hospital with strict protocols and teaching methodologies can achieve inguinal hernia repair outcomes comparable to those of dedicated hernia centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Inguinal hernia is the most common hernia among abdominal wall hernias [ 1 , 2 ]. Inguinal hernia can range from being asymptomatic to painful especially with coughing, exercise, or bowel movement [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inguinal hernia is the most common hernia among abdominal wall hernias [ 1 , 2 ]. Inguinal hernia can range from being asymptomatic to painful especially with coughing, exercise, or bowel movement [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 1 month follow up, 9 patients (18%) complained of pain at operated site, at 3 month follow up 7 patients (14%) complained of pain at operated site and at the end of 1 year follow up 3 patients (6%) complained of pain at operated site. )3 (6) As shown in Figure 1, no recurrence of hernia has been found at the end of our 1 year follow up.…”
Section: As Shown Inmentioning
confidence: 61%
“…showed that in open hernia repair, lichtenstein tension free repair is superior to traditional tissue approximation methods. 6,7 Lichtenstein's tension free mesh repair is the most commonly performed in open inguinal hernias.…”
Section: Introductionmentioning
confidence: 99%